Ventilasi dan Perfusi, serta Hubungan antara Ventilasi dan Perfusi: [Ventilation, Perfusion, and Its Correlation in Pulmonary Diagnostic] - Afrita Amalia Laitupa; Muhammad Amin (Faculty of Medicine Universitas Airlangga, 2016)
Lung is a place for gas exchange where ventilation and perfusion occurs. Ventilation is the first step where sequential process of inhalation and exhalation take place. Meanwhile perfusion as the other step facilitates the gas exchange and tissue supply need. Blood flows through the lungs are equals as the amount of cardiac output where the factors that control cardiac output are mainly peripheral factors, also control pulmonary blood flow. In general condition, pulmonary blood vessels act as a passive tube, which can be increased with the increasing pressure and narrowed the pressure drop. Oxygen absorption level from lungs into bloodstream is a critical determinant for functional capacity, and an important factor wheter in normal conditions (including exercise) or even in illness state. Lung diffusion capacity is influenced by several geometric and functional factors. Gravitation influence systematic gradient in ventilation and perfusion distribution. Ventilation and blood flow variations at horizontal level also occur due to intrinsic anatomic variations and vascular geometry, as well as the differences in airway and vascular smooth muscle response which modifies the distribution. The change of integrity intrapleural chamber, hydrostatic pressure and osmotic imbalance, malfunction of surfactants, other intrinsic weakness of the branching system in the form of a progressive airway, and all the things that could potentially damage the structure of the lung can cause ventilation and diffusion dysfunction.